Investigational New Drug Application and Approval Process - Menda, Irfan Siraj (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe investigational new drug (IND) application is the result of a successful preclinical development program. The IND is also the vehicle through which a sponsor advances to the next stage of drug development known as clinical trials (human trials). This article will focus the approval process of investigational new drug & its approval by regulatory bodies.IND Application is the precursor of NDA Process. This article, which emphasis on easy access to understanding how this agency (USFDA) operates with respect to practical aspect of IND & its approval process. USFDA establish process albeit need to improve IND Application process.